STUDI PERBANDINGAN SIFAT-SIFAT MINYAK KENANGA DARI BLITAR, BOYOLALI DAN CIREBON - Bambang Wiyono; Mohammad Rosid (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
The purpose of this research is to compare the phvsico-chemical properties of cananga oil from Blitar, Boyolali, and Cirebon with the Indonesian Insutrial Standard requirement. Cananga oils are obtained from the distiller in Blitar and Boyolali regencies. The distilling method used in these regencies are cohobations. The distilling time was 40 hours in Blitar and 36 hours in Boyolali, whereas, cananga oil properties from Cirebon was based on the literature. To find out the difference in properties, the student's t-test was applied.The results indicated that colour (visual), specific gravity, refractive index, ester number, and ester content of cananga oils from Blitar, Boyolali, and Cirebon have met Indonesian Industrial Standard requirement (Sll. 0026 - 73), except for the ester number and ester content of cananga oil from Boyolali. Based on the ester number, cananga oil from Cirebon had a better quality than that of Blitar or Boyolali. Cananga oil from Boyolali had the lowest quality. Crushing cananga flowers before distilling, decreased the ester number, ester content, and yield of the resulting oil. Therefore, the crushing of raw of the cananga flowers prior to processing was found unnecessary.